Adenosine A2A Receptor Suppressed Astrocyte-Mediated Inflammation Through the Inhibition of STAT3/YKL-40 Axis in Mice With Chronic Cerebral Hypoperfusion-induced White Matter Lesions - Yuan, Jichao; Chen, Lin; Wang, Jie; Xia, Simin; Huang, Jialu; Zhou, Linke; Feng, Chengjian; Hu, Xiaofei; Zhou, Zhenhua; Ran, Hong (Frontiers in Immunology, 2022)
White matter lesions are an important pathological manifestation of cerebral small vessel disease, with inflammation playing a pivotal role in their development. The adenosine A2a receptor (ADORA2A) is known to inhibit the inflammation mediated by microglia, but its effect on astrocytes is unknown. Additionally, although the level of YKL-40 (expressed mainly in astrocytes) has been shown to be elevated in the model of white matter lesions induced by chronic cerebral hypoperfusion, the specific regulatory mechanism involved is not clear. In this study, we established in vivo and in vitro chronic cerebral hypoperfusion models to explore whether the ADORA2A regulated astrocyte-mediated inflammation through STAT3/YKL-40 axis and using immunohistochemical, western blotting, ELISA, PCR, and other techniques to verify the effect of astrocytes ADORA2A on the white matter injury. The in vivo experiments showed that activation of the ADORA2A decreased the expression of both STAT3 and YKL-40 in the astrocytes and alleviated the white matter injury, whereas its inhibition had the opposite effects. Similarly, ADORA2A inhibition significantly increased the expression of STAT3 and YKL-40 in astrocytes in vitro, with more proinflammatory cytokines being released by astrocytes. STAT3 inhibition enhanced the inhibitory effect of ADORA2A on YKL-40 synthesis, whereas its activation reversed the phenomenon. These results suggest that the activation of ADORA2A in astrocytes can inhibit the inflammation mediated by the STAT3/YKL-40 axis and thereby reduce white matter injury in cerebral small vessel disease.